Development of LEKER SIRA E-LKPD on Nganggung Tradition to Enhance Learning Outcomes and Religious Values in Class X Social Studies at SMA 1 Pemali - Sulistia, Sulistia; Widiadi, Aditya Nugroho; Agung, Dewa Agung Gede (Yupa: Historical Studies Journal, 2024)
In the process of learning in schools, teachers, students, media, and the environment form a complex interplay. The role of teachers becomes more challenging as students heavily rely on them, leading to ineffective learning. Due to this dependence, a solution can be found by utilizing instructional materials that help teachers facilitate independent learning for students. This research aims to produce "LEKER SIRA" to enhance learning outcomes and religious character values in the history lessons of Grade X Social Studies at SMAN 1 Pemali. The research adopts the ADDIE research model. Based on the findings, it is concluded that "LEKER SIRA" is highly suitable as instructional material for Indonesian history lessons. The school-based research indicates an improvement in learning outcomes, with the average increasing from 51.8 to 89.9. This suggests that all students have achieved proficiency. According to the questionnaire on religious character values, a percentage of 81.8% was obtained.